MicroRNAs and esophageal cancer - Patnaik, Santosh Kumar (Pioneer Bioscience Publishing Company, 2010)
Cancer of the esophagus is a highly aggressive disease associated with an overall poor prognosis. There is an insistent need for improving our understanding of the molecular basis of this disease. The recent emergence of observations on the role of microRNAs in cancer and their potential as biomarkers has prompted many investigations to examine their relevance to esophageal cancer. This article provides an introduction to microRNA biology and the techniques involved in studying them, and summates what is now known about their role and utility in regard to neoplastic esophageal diseases.